1966
DOI: 10.3181/00379727-122-31248
|View full text |Cite
|
Sign up to set email alerts
|

On Insulin Immunologic Activity in Livers and Kidneys of Mice Injected with Beef Insulin.

Abstract: INSULIN-IMMUNOASSAY ESTIMATED RECOVERY nomena are related. Perhaps the large initial inhibition of leucine catabolism compensates for whatever anabolic inhibition is occurring. Since less leucine i s being degraded, more is available for incorporation and this effect counteracts the process of inhibition of protein synthesis. Once the catabolic inhibition reaches a plateau, the compensation no longer exists, and the inhibition of protein anabolism can assert itself. This hypothesis represents one possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1967
1967
1975
1975

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…In respect to simplicity, AIS-i25 I estimations are practically as easy to secure as are estimations of TCA insoluble radioiodine, the criterion which has been so much used for "estimation" of "intact radioiodoinsulin" [for references cf Lee (8)]. Good specificity is indicated both by theory and by present findings that AIS-m I disappeared from mouse plasma, kidney and liver appreciably more rapidly than did TCA insoluble 125 I; this agrees with literature reports that no matter whether tissue "insulin" was estimated as insulin radioiodine peaks on paper (7,9), through bio-assay (9), or through immunoassay (10,11), this tissue "insulin" always disappeared more rapidly than did TCA insoluble radioidoine derived from iv injected insulin-131 ! or -125 I.…”
Section: Discussionsupporting
confidence: 90%
“…In respect to simplicity, AIS-i25 I estimations are practically as easy to secure as are estimations of TCA insoluble radioiodine, the criterion which has been so much used for "estimation" of "intact radioiodoinsulin" [for references cf Lee (8)]. Good specificity is indicated both by theory and by present findings that AIS-m I disappeared from mouse plasma, kidney and liver appreciably more rapidly than did TCA insoluble 125 I; this agrees with literature reports that no matter whether tissue "insulin" was estimated as insulin radioiodine peaks on paper (7,9), through bio-assay (9), or through immunoassay (10,11), this tissue "insulin" always disappeared more rapidly than did TCA insoluble radioidoine derived from iv injected insulin-131 ! or -125 I.…”
Section: Discussionsupporting
confidence: 90%
“…Elgee and Williams (25) have shown that preloading with insulin diminished the rate of insulin-131I degradation in vivo, and that the extent of inhibition was the same regardless of whether the preloading was accomplished with labeled or unlabeled insulin, implying that both types of insulin competed equally well for the degradation system. Beck, Roberts, Blanken-baker, and King (26) have shown that the distribution and rates of accumulation of labeled and unlabeled insulin in various organs and subcellular fractions were similar. Finally, Samols and Ryder (27) have shown that hepatic clearance of exogeneously administered beef insulin was similar to the clearance of endogenous human insulin in human subjects.…”
Section: Discussionmentioning
confidence: 94%
“…Beck et QZ. (15) have recently shown that intact insulin molecules can penetrate the liver cells of mammals. The degradation of insulin in the liver apparently is not total, and this suggests that the liver not only shows a capacity for "taking up" radioactivity from the blood, but can also retain undegraded insulin.…”
Section: Hours Of the Experimentmentioning
confidence: 99%